A Literary Review of Asrigdara in Ayurved w.s.r. to Menometrorrhagia - Kumari, Sonu; Dixit, Mahesh; Meena, Narendra Kumar (International Research Journal of Ayurveda & Yoga, 2021)
In Prasuti tantra OPD, Menometrorrhagia is the most common gynaecological illness. It is a symptom that can be detected in the majority of gynecological issues. The irregular, massive blood loss per vaginum is a symptom of abnormal uterine bleeding . Bleeding in excess of regular amounts and for a longer period of time during the menstrual cycle. Abnormal uterine bleeding is known as Asrigdara in Ayurvedic samhitas, which implies pradirana (extreme excretion) of raja (menses) per vaginum . The causative factor or Dosa In Asrigdara is Vayu, and the vitiated Dhatu Or Dusya is Rakta (blood), or blood is also vitiated . Because the qualities of rakta and pitta are so similar, vitiating Rakta would aggravate pitta as well. As a result, management should be centered on the usage of medications with Kashaya Rasa and Pittashamak Guna. Due to its Stambhana feature, Kashaya rasa is mostly used to treat bleeding symptoms. There is loss of Rakta Dhatu, so we use the drugs and diet that increases Rakta Dhatu. Management mainly based on the principle of Raktastambhaka and Raktavardhaka.